Study on the Time-varying Mesh Stiffness of Speed-increasing Gear Pair with Non-uniform Wear - He Zeyin; Tang Weiyi; Lin Tengjiao; Sun Shizheng (Jixie chuandong)
Taking an involute cylindrical speed-increasing gear pair as the research object, the tooth surface contact pressure and the relative sliding velocity are deduced to establish the non-uniform wear model of the spur gear pair based on the Hertz contact theory and the Archard’s wear formula. And the tooth surface wear depth under different cycles is calculated. Then, based on the potential energy method, the non-uniform wear time-varying mesh stiffness formula of spur gear under different positions of base circle and root circle is developed. The effect of non-uniform wear on the time-varying mesh stiffness is studied. The results show that the wear depth is unevenly distributed on the involute profile, the wear around the pitch circle is the smallest, the wear depth at the tooth root and addendum is larger, and the cumulative wear depth at the top of the tooth is the largest. As the number of cycles increases, the time-varying meshing stiffness of the gear decreases with the increase of the wear depth. The stiffness reduction of the double-tooth meshing zone is greater than that of the single-tooth meshing zone.